Elementi chimici strategici e critici - Olmi, Fabio (Chimica nella Scuola, 2024)
The article deals with the problem of strategic and critical materials, explaining their meaning and listing the today 34 critical raw materials. Then it addresses the European situation and focuses on the issue and the measures taken to reduce Europe’s strong dependence on third countries. The situation of Italy in this field is also presented. Finally, some examples of critical raw materials are examined, discussing the future need to their recycling on a large scale.